A randomized controlled trial to evaluate the efficiency of laminated alginate impression in upper complete denture fabrication. - علوان, علي; محمود محمود (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: One of the most important and difficult challenges facing the prosthetist is complete denture's stability, which is provided by good fit in the final impression stage. Aim: This study aims to evaluate upper complete dentures bases' retention when using Laminating alginate impression as final impression technique in comparison with the traditional techniques. Materials and Methods: thirty completely upper edentulous patients were selected to evaluate the retention of acrylic denture bases provided by two final impression techniques (The first impression was recorded using traditional technique with low-fusion compound as border molding and zinc oxide eugenol (ZOE) past as final impression, the second impression was recorded using laminated alginate technique as final impression). Results: Statistical analysis results showed that there were no differences in upper complete dentures bases' retention between the two used techniques. Conclusions: The laminated alginate technique provided similar clinical retention on dentures' bases compared to the traditional technique.